Perkembangan Islam di Indonesia Era Reformasi - M Sauki (LPPM IAIN Sorong, 2018)
Islam in Indonesia has existed since in the 7th and became more widespread in the 13th. The success of Islam spread in Indonesia including the most dynamic with the method of cultural and political da'wah. Since the era of independence, Islam has grown rapidly. This paper aims to examine the existence of Islam in Indonesia today, with a review before the reform era and after reform. The Islamic movement can be said to be very influential on Indonesia's independence. This is evident from the role of Islamic organizations and parties. Despite its dominant influence, Islam did not become the official ideology of the Indonesian state after independence, as in the events of the Jakarta Charter, Islamic leaders preferred Pancasila as the principle of a pluralistic state. Uniquely, despite the predominantly Muslim population, Islam is not formally exposed in the system of government. After the Reform Era, many new Islamic parties and organizations were established. In Islamic conception, in general, reform is understood as ishlāh, which is in the ushul fiqh rules